On the motion of a hydro-mechanical system with a viscous liquid under periodic influences - V. L. Sennitskii (Учёные записки Казанского университета: Серия Физико-математические науки, 2025)
The problem of the motion of a hydro-mechanical system consisting of a viscous liquid and solid bodies, a wall and a plate, bordering it is formulated and solved. The wall undergoes a prescribed translational motion, and its boundary is permeable to the liquid. The hydro-mechanical system is subjected to time-periodic influences. The problem formulation includes the equation of the plate motion, the Navier–Stokes equation, and the conditions at the solid–liquid interfaces. New hydro mechanical effects are revealed.